Поросенок Бейб: [сказка] / Д. Кинг - Смит ; [художник А. Шер] - Кинг-Смит Д. (Новые сказочные повести, 2008)
Экземпляры: Д.О. (20200708) / Инвентарный номер: 41985 / Сис.шифр: 84(4 Вел) / Авт.знак: К 41 / ГРНТИ: 17.82 / ББК: 84(4 Вел)